Elements of literature : essay, fiction, poetry, drama, film - Scholes, Robert (Oxford University Press, 1991)
Providing the most thorough coverage available in one volume, this comprehensive, broadly based collection offers a wide variety of selections in four major genres, and also includes a section on film. Each of the five sections contains a detailed critical introduction to each form, brief biographies of the authors, and a clear, concise editorial apparatus. Updated and revised throughout, the new Fourth Edition adds essays by Margaret Mead, Russell Baker, Joan Didion, Annie Dillard, and Alice Walker; fiction by Nathaniel Hawthorne, Ursula K. LeGuin, Anton Chekov, James Joyce, Katherine Mansfield, F. Scott Fitzgerald, William Faulkner, Alice Walker, Louise Erdrich, Donald Barthelme, and James McPherson; poems by John Donne, Robert Browning, Walt Whitman, Edwin Arlington Robinson, e.e. cummings, Langston Hughes, W.H. Auden, Philip Levine, and Louise Gluck; and plays by August Wilson, Marsha Norman, Wendy Wasserstein, and Vaclav Havel. The chapter devoted to film examines the relation of film to literature and gives the complete screenplay for Citizen Kane plus close analysis of a scene from the film. With its innovative structure, comprehensive coverage, and insightful and stimulating presentation of all kinds of literature, this is an anthology readers will turn to again and again.